Terapia do diabetes mellitus em cães - Santos, Antônia Fabiana da Silva [UNESP] (2011)
Diabetes Mellitus is caracterized by a disturbance on endocrine pâncreas with reduction in serum levels of insulin. The deficiency or absence of insulin promotes alterations in the metabolism of carbohydrates, lipidis and proteins. The most common clinical signs of disease are polyuria, polydipsia, polyphagia and loses of weight. The diagnosis is made based on clinical symptoms, with laboratory confirmation through persistent hyperglycemia on fasting and glycosuria. Treatment includes insulin therapy, diet, exercise and oral hypoglycemic agents in an attempt to reverse the catabolic effects associated with deficiency or antagonism of insulin and restore normal homeostasis of the metabolism of proteins, lipids and carbohydrates